EKSISTENSI PELA GANDONG SEBAGAI CIVIC CULTURE DALAM MENJAGA HARMONISASI MASYARAKAT DI MALUKU - Yakob Godlif; Samuel Patra (Sosio-Didaktika: Social Science Education Journal, 2018)
Current new globalisation cause mindset and more modern Maluku community personalities and individualists, so as though pela gandong as cultures that executed it is no longer meaningful. Its negative impact on the next generation of Maluku, most did not know the deeper culture pela gandong. Whereas, pela gandong is cultural heritage treasure even for the younger generation of Maluku. The legacy of cultural citizenship as pela gandong has been evenly distributed across all of the cultural community of Maluku and very urgent because it is not found in the community or other areas in Indonesia. Pela gandong as civic culture is a main pillar to keep the harmonization within the community of Maluku, given the potential conflict in the Maluku, as occurred in 1999-2000, then it becomes an obligation for the holder to give all stace full attention to culture pela gandong.